2006
DOI: 10.1186/1746-160x-2-43
|View full text |Cite
|
Sign up to set email alerts
|

Histological analysis of the effects of a static magnetic field on bone healing process in rat femurs

Abstract: Background: The aim of this study was to investigate, in vivo, the quality of bone healing under the effect of a static magnetic field, arranged inside the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 15 publications
3
36
1
Order By: Relevance
“…During vibration, the noise produced by the platform was minimal. The intensity of the static magnetic field generated by the platform was measured to be below 1 Gauss on the platform, which was far below the intensity reported to have osteogenic effects [30][31][32][33][34] or the safety level recommended by the Institute of Electrical and Electronics Engineers (IEEE). The thermal effect of the platform was not detected either on the platform surface or within the rat cage after 48 h of continuous running test.…”
Section: Methodsmentioning
confidence: 87%
“…During vibration, the noise produced by the platform was minimal. The intensity of the static magnetic field generated by the platform was measured to be below 1 Gauss on the platform, which was far below the intensity reported to have osteogenic effects [30][31][32][33][34] or the safety level recommended by the Institute of Electrical and Electronics Engineers (IEEE). The thermal effect of the platform was not detected either on the platform surface or within the rat cage after 48 h of continuous running test.…”
Section: Methodsmentioning
confidence: 87%
“…The present study followed the research line established by Puricelli [14]. As in many other experimental studies, the rat was used as a model, due to its advantages in terms of ease of acquisition, maintenance and surgical manipulation [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…SMF has been studied as a noninvasive physical treatment for promoting bone growth and bone healing, and preventing bone loss (Zhang et al, 2014a). Animal studies have revealed that certain SMFs have a synergistic role in such circumstances as bone surgical invasion (~50 mT) (Yan et al, 1998), ischemic bones (~50 mT) (Xu et al, 2001), ovariectomized rats (180 mT) (Xu et al, 2011), adjuvant arthritis rats (30-80 mT) (Taniguchi et al, 2004), bone fracture (4 mT) (Puricelli et al, 2006) and bone grafts (4 mT) (Puricelli et al, 2009). Most cellular studies indicate that the anabolic effects on bone homeostasis are due to the enhanced activities of osteoblast and promoted osteogenic differentiation in mesenchymal stem cells, although the underlying mechanisms of SMF effects on cell activities are still unclear (Colbert et al, 2009;Markov, 2007).…”
Section: Introductionmentioning
confidence: 99%